2020
DOI: 10.1007/s40200-020-00496-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the consumption of natural products on some biochemical parameters of a type 2 diabetic population

Abstract: Purpose The use of phytotherapy is common worldwide and especially in Algeria. This practice was transmitted orally and ritually to treat chronic diseases. Safe extracts of edible plants can provide a resource of structurally diverse molecules that can effectively interfere with multifactorial diseases, such as diabetes mellitus. The objective of this work is to study the biochemical parameters of diabetic populations who consume medicinal plants. Methods This study involved 100 T2D subjects, recruited over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Our results of significant reduction of blood glucose levels in diabetic rats by administration of herbal extract was in accordance with earlier reported results of similar nature [27,28]. Few studies were reported on the effect of supplementation of cinnamon and other herbs in type 2 diabetic populations proved to be effective in glycemic control [9,10]. The metabolites present in cinnamon namely cinnamaldehyde and methyl hydoxychalcone polymer were reported to have insulin-mimetic properties [29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…Our results of significant reduction of blood glucose levels in diabetic rats by administration of herbal extract was in accordance with earlier reported results of similar nature [27,28]. Few studies were reported on the effect of supplementation of cinnamon and other herbs in type 2 diabetic populations proved to be effective in glycemic control [9,10]. The metabolites present in cinnamon namely cinnamaldehyde and methyl hydoxychalcone polymer were reported to have insulin-mimetic properties [29][30][31].…”
Section: Discussionsupporting
confidence: 92%